Assessment of Nanosilymarin's Therapeutic Efficacy in Mitigating CCl4-Induced Hepatotoxicity in Rats - Nisreen Jasim (Basrah Journal of Veterinary Research)
Drug and chemical substances are common causes of liver dysfunction, including acute hepatitis and liver failure. Carbon tetrachloride (CCl4) is widely used as a model to study hepatic toxicity. Nanosilymarin (S-CsNPs), with its antioxidant properties, has emerged as a potential therapeutic agent for liver injury. This study aims to evaluate the therapeutic effect of (S-CsNPs) on hepatotoxicity. The study involved 30 adult female albino rats, randomly divided into five groups. The first group served as the negative control and received no treatment. The second group received carbon tetrachloride (CCl4) intraperitoneally at a dose of 3 mL/kg twice weekly for four weeks. The third group was the untreated group, which also received CCl4 as described but did not receive any subsequent treatment. The fourth group was treated with silymarin at a dose of 50 mg/kg, administered orally once daily for three weeks following CCl4 exposure. The fifth group received (S-CsNPs) at a dose of 0.2 mg/rat, administered orally once daily for three weeks after CCl4 administration. Liver function was assessed via enzyme markers (ALT, AST, ALP, GGT and bilirubin), and oxidative stress was evaluated by measuring TNF-α, MDA, SOD, and GSH levels. The CCl4 group showed significant elevations in liver enzymes and oxidative stress markers compared to negative controls. Treatment with (S-CsNPs) significantly(P<0.05) reduced ALT, AST, ALP, GGT, bilirubin, TNF-α, and MDA levels, while increasing SOD and GSH levels compared to CCl4, untreated and silymarin-treated groups. Nanosilymarin effectively reduced CCl4-induced liver damage, indicating its potential as a liver-protective agent